Pemodelan Background Traffic Pada Jaringan Berkapasitas Terbatas - Jay Idoan Sihotang (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2019)
Rapid technological developments influence various aspects of life. And that makes the use of Internet technology as a part of carrying out daily activities. But the need for adequate Internet networks is hampered by limited bandwidth capacity in the network. Measurements made on limited capacity testing networks aim to determine the characteristics of the testing network and the rate of traffic in the network. In the testing network, the average bandwidth capacity was 3.61 Mbps, and the average rate of traffic was 1,428 Mbps. The rate of traffic that occurs in the testing network is worth 1/3 of the highest bandwidth capacity on the testing network which is 4,76 Mbps. With the characteristics of continuous packet delivery of 70%, and bulk packet delivery by 30%. Through the results of the characteristics of the package delivery, the background traffic model that is constructed describing the transmission of bulk packets will be transmitted after 7 continuous packets sent. Background traffic modeling can be a reference in conducting content delivery simulations in network simulations application that resemble the characteristics of testing network